Perception of threats and related management measures: The case of 32 marine protected areas in West Africa. (July 2020) - Failler, Pierre; Touron-Gardic, Grégoire; Drakeford, Benjamin; Sadio, Oumar; Traoré, Marie-Suzanne
Abstract: This paper presents the results of surveys conducted with managers of West African Marine Protected Areas (MPAs) and focuses on the threats and the extent to which they are taken into account in the management process. The data and information derived from the surveys are used to provide a reference situation and to develop a complete inventory of threats faced by MPAs in the region. MPA managers identified unmanaged fisheries, coastal erosion, overexploitation of natural resources and pollution as the main threats to the sustainability of MPAs in the region. Climate change, although considered to be diffuse, is also a concern for managers. However, management measures are aimed (predominantly) at preventing overfishing and the overexploitation of terrestrial natural resources. Therefore, coastal erosion, pollution and climate change are only indirectly (and marginally) targeted by these management measures. Moreover, the management measures implemented i.e. monitoring, awareness raising and surveillance are insufficient and mainly aligned with the capacity of the local institutions. However, what is actually needed is more far reaching and adaptive actions to mitigate the current threats. The low financial, technical and human resources largely explain the limited scope of management actions taken. Coupled with the information and data deficit, which increases the inertia regarding threats that have been recurrent for more than a decade, management measures have not been sufficient in managing MPAs in the region. This paper recommends that the links between pressures on MPAs, technical recommendations and resulting management actions must be reinforced.